Pengaruh Marketing Mix-7P Terhadap Kepuasan Nasabah BRI Syariah Kantor Cabang Malang - Larasati, Diani Ajeng; Seno Aji, Toni (Jurnal Ekonomika dan Bisnis Islam, 2019)
The aim of this research is to find out whether the marketing mix affect to customer satisfaction in BRI Syariah branch office Malang. This research uses associative quantitative methods. The sample used in this study amounted to 100 respondents who came from Malang branch BRI Syariah customers and used accidental sampling techniques.The Questionnaires used a Likert scale.The results of this study indicate that place, process, and physical evidence variables affect on customer satisfaction, while product, price, promotion and people has not been affecting the customer satisfaction at the BRI Syariah branch office Malang.